(untitled) (Research, Society and Development, 2020)
The contamination scenario of Covid-19 causes concern in society, economics and in the scientific field. Because it is recent, detected in China for the first time in December 2019, and in Brazil on February 26, 2020, the scientific results still lack consistency to point out feasible elements of better measures to be carried out. The present study aims to analyze Covid-19 control practices adopted by municipal governments to contain the spread of the disease. The efforts of the scientific field and health organizations point to the need for social isolation as a practice to face the disease. On the other hand, such a practice affects countries’ economic productivity. From a documentary analysis, it is noted that Ubá, a Brazilian country side City, opted for a more flexible disease prevention model, while Viçosa adopted strict measures to combat the Covid-19 transmission. opting for access restriction and circulation in the city.